Physical properties of concrete with Rice Husk Ash (RHA) as mineral admixture and crushed ceramic tiles as replacement to coarse aggregates / Siti Nur Aishah Mohd Noor ... [et al.] - Mohd Noor, Siti Nur Aishah; Roslan, Rohasnita; Zaiha Zainol, Norrazaman; Syed Jamaludin, Shariffah Zatil Hidayah (2021)
Rice Husk Ash (RHA) is an agro-waste material that is highly produced in Malaysia over the year containing high amorphous silica which can improve the performance of the concrete. It is economical to be used in partial replacing or as mineral admixture in the Ordinary Portland Cement. Meanwhile, the waste from the ceramic tiles is beneficial to be used in concrete as coarse aggregates replacement due to its characteristic of ceramic tiles which are hard and durable. This research intended to study the effect of physical properties of RHA as mineral admixture for cement in concrete and also the effect with addition of crushed ceramic tiles (CCT). In this study, the RHA has been replaced at 10% by mass of cement as mineral admixture with various percentages of CCT as coarse aggregates starting from 0%, 5%, 10% and 15%. Workability, density and water absorption tests have been conducted to study the physical properties of the concrete. The results obtained show that 10% is the optimum percentage for CCT in concrete with 10% of RHA.